An Exploration into the Qurâanic Evidence of the Legal Ruling on the Alteration of Allahâs Creation in Newly-emerged Medical Issues - Ã˜ÂµÃ˜Â¨Ã˜Â§Ã˜ÂºÃ›ÂŒ Ã™Â†Ã˜Â¯Ã™ÂˆÃ˜Â´Ã™Â†, Ã™Â…Ã˜Â±Ã›ÂŒÃ™Â…; Ã˜Â³Ã™Â„Ã˜Â·Ã˜Â§Ã™Â†Ã›ÂŒ, Ã˜Â¹Ã˜Â¨Ã˜Â§Ã˜Â³Ã˜Â¹Ã™Â„Ã›ÂŒ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
The occurrence of newly-emerged and unprecedented phenomena in various medical fields raises questions as to their legality or illegality. Despite the fact that one of the most important evidences of the jurists in this regard is the verse on alteration of creation, which because of absolute disapproval provides initial ground for unlawfulness, some, however, by modifying the absoluteness of the verse have dedicated the alteration of the unlawful to the legislative alterations; and as a result have believed in lawfulness because of withdrawal of creational alterations from the referent of the verse, whereas there is no reason for withdrawal of creational alterations from the referent of the verse. In contrast, many of the SunnÄ« jurists have generally issued legal decisions to the unlawfulness of such phenomena, resulting from lack of accurate conception of the subject and untrue impression about the concept of alteration of creation; whereas it is possible to approve lawfulness while preserving the absoluteness. With the descriptive-analytical method and using interpretations and traditions and with the aim of accurate recognition of one of the key concepts of the Qurâan, the above research intends to analyze and examine the subject (mutaâallaq) of the unlawfulness mentioned in the verse by avoiding going on any extremes and, as far as possible, through preserving the verseâs designative manifestation, so that by determining the yardstick of prohibition (taá¸¥rÄ«m), the instances lacking proof would be excluded from the referent of the verse. Because, despite the absoluteness of the verse, the subject of prohibition is not alteration âin its own rightâ; rather, it is alteration of âAllahâs creationâ due to its attribution to Allah in terms of issuance aspect. And since the action issued by Allah consists of the feature of perfection seeking and prudence and contains beauty, or rather the most beauteous, thus any alteration opposing the above features is forbidden and the rest are out of prohibition criterion.